The association Between Occupational Exposure to silica and Risk of Developing Rheumatoid Arthritis: A Meta-Analysis - Fereshteh Mehri; Ensiyeh Jenabi; Saeed Bashirian; Farshid Ghorbani Shahna; Salman Khazaei (Elsevier, 2020)
Background: Rheumatoid arthritis (RA) is an autoimmune disease with systemic inflammatory arthritis. This meta-analysis was conducted to examine the association between occupational exposure to silica and the risk of developing RA among different workers. Methods: In this meta-analysis, we searched relevant published studies using major electronic databases including Scopus, PubMed, ISI Web of Science, and Google Scholar search engine up to October 2019, and the references of retrieved articles were also checked for further possible sources. A random-effects model was used to account for heterogeneity among the results of the studies using the pooled odds ratios (ORs) and their 95% confidence intervals (CIs). The Q-statistic and I2 tests were calculated to assess heterogeneity between the studies. Results: The pooled calculation of OR indicated a significant association between occupational exposure to silica and risk of developing RA among different workers (OR = 2.59, 95% CI = 1.73 to 3.45). In addition, the pooled estimates of OR in smokers were statistically significant (OR = 2.49, 95% CI = 1.13 to 3.86). Conclusions: The findings of the present study reveal that occupational exposure to silica may be associated with increased risk of developing RA.